Development of a “Power of Yet” Educational Package for Underachieving Gifted Students - Amanimovahed , Narjes; Bahramipour Esfahani, Mansoureh; Yousefi , Zahra (Psychological Research in Individuals with Exceptional Needs, 2026)
The aim of this study was to develop a “Power of Yet” educational package for underachieving gifted students. This qualitative study employed thematic analysis using a deductive (theory-driven) approach and Attride-Stirling’s technique. Accordingly, based on research literature related to growth mindset, Dweck’s theory of intelligence beliefs, and the concept of the “Power of Yet,” 35 sources—including books, articles, master’s theses, and doctoral dissertations—published between 2016 and 2025 were selected through purposive sampling based on the criterion of theoretical saturation. These sources were retrieved from reputable national and international databases, and themes relevant to the field were extracted. Thematic analysis was conducted manually using a systematic coding procedure. The analysis identified 22 basic themes, 12 organizing themes, and five global themes: learning challenges, acceptance of errors and mistakes, insight and attitudes toward the self, determination and enthusiasm for success, and resilience and risk-taking. Subsequently, based on the resulting conceptual framework, an eight-session “Power of Yet” educational package was developed. To assess the content validity and credibility of the educational package, the Content Validity Ratio (CVR) was calculated based on the evaluations of six experts. A CVR of 1.00 was obtained, indicating an acceptable level of content validity and complete agreement among the evaluators. The findings showed that the “Power of Yet” educational package incorporates the components of learning goal setting, acceptance of failure as an opportunity, use of “yet” as verbal feedback, self-determination, modeling successful individuals, persistence and flexibility in the face of obstacles, and risk-taking for personal growth and change. Based on these findings, it can be concluded that this educational package is appropriate for enhancing the “Power of Yet” among underachieving gifted students.